STRATEGI PENGEMBANGAN EKOWISATA BAHARI PULAU PALAMBAK KABUPATEN ACEH SINGKIL PROVINSI NANGGROE ACEH DARUSSALAM - Jasman '; Syofyan Siregar; Rifardi ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
This study was conducted on May 27 to June 3, 2013 on the island of Aceh Singkil Palambak Nanggroe Aceh Darussalam. The purpose of study is to analyze the potential of tourism in Palambak as a marine tourism in the concept of ecotourism as well as analyze and formulate concepts and strategies Palambak Island marine tourism development.Based on the analysis, the island has hight potential to serve as a national and international marine ecotourism based on the aspects of chemical physics parameters oseonografi, geology and geomorphology, depth and slope of the beach, type of beach substrate, climate coastal ecosystems, historical value, based on an overview tour players, and the values of WTP and WTA. The concept of ecotourism (ecoturism). Can be applied to the develop marine tourism island based on strategy of SO, WO, ST and WT.Keywords: Palambak Island, marine ecotourism, potential and strategies